A rare case of multilocular cystic renal neoplasm of low malignant potential diagnosed on intra-operative fine needle aspiration cytology - Patel, Mandakini M.; Gamit, Bhavna N.; Patel, Sharmishtha I.; Patel, Mubin I.; Gandhi, Priyanka S. (International Journal of Research in Medical Sciences, 2019)
Multi-locular Cystic Renal Cell Carcinoma (MCRCC) is now considered as Multilocular cystic renal neoplasm of low malignant potential (MCRNLMP) in World health organisation classification (WHO) 2016. It is usually seen in elderly people where it can mimic most of the time as benign cystic lesion. Authors are reporting a case of MCRNLMP in a 70 year male diagnosed intraoperative with the help of Fine Needle Aspiration Cytology (FNAC). Radiological and other clinical findings are in favour of cystic renal lesion. And it is very important to differentiate it from conventional renal cell carcinoma which requires radical nephrectomy. So, radiological finding and FNAC is instrumental in diagnosing this rare case which require different mode of surgical management.